Recovery of Dysphagia in Lateral Medullary Stroke - Hitesh Gupta; Alakananda Banerjee (Case Reports in Neurological Medicine)
Lateral medullary stroke is typically associated with increased likelihood of occurrence of dysphagia and exhibits the most severe and persistent form. Worldwide little research exists on dysphagia in brainstem stroke. An estimated 15% of all patients admitted to stroke rehabilitation units experience a brainstem stroke out of which about 47% suffer from dysphagia. In India, a study showed that 22.3% of posterior circulation stroke patients develop dysphagia. Dearth of literature on dysphagia and its outcome in brainstem stroke particularly lateral medullary stroke motivated the author to present an actual case study of a patient who had dysphagia following a lateral medullary infarct. This paper documents the severity and management approach of dysphagia in brainstem stroke, with traditional dysphagia therapy and VitalStim therapy. Despite being diagnosed with a severe form of dysphagia followed by late treatment intervention, the patient had complete recovery of the swallowing function.